STORE ATMOSPHERE SEBAGAI STIMULI MINAT BELI KONSUMEN GENERASI Y - DHARMA, AYUSTA WIDYA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Proliferation of modern shopping malls today have changed the pattern of consumer spending, window shopping activities are activities that are most often committed by mall visitors, this activity is identical with generation Y consumers. Generation Y consumers have greater economic power than other generations, when the retailer is able to reach more consumers generation Y acquired profits will be higher. Store atmosphere is one strategy that can be used to attract generation Y consumers. Atmospheric instrumental attract buyers and make them comfortable, the atmosphere is in the sense of the atmosphere that is created from the combined elements of store design, including visual communication, lighting, color, and aroma.